Optimizing motorcycle tire tread patterns to mitigate hydroplaning: Development and validation of a predictive mathematical model - Weerachai Chaiworapuek; Ravivat Rugsaj; Chakrit Suvanjumrat (Transportation Engineering)
Hydroplaning is a critical hazard for motorcyclists, often resulting in severe injuries or fatalities, particularly on wet road surfaces and at elevated speeds. This study presents advanced methodologies to evaluate hydroplaning force, aiming to mitigate these risks and optimize motorcycle tire tread patterns. A state-of-the-art hydroplaning testing apparatus was developed to precisely measure tire behavior on wet surfaces under controlled conditions. Comprehensive analyses of various tire tread patterns were conducted to identify key parameters influencing tire-to-ground contact. Leveraging these insights, a refined mathematical model was formulated to predict the tire contact area, achieving a minimal error margin of 5.72 %. This model was integrated into a hydroplaning force equation that accounts for velocity, tire inflation pressure, supporting load, and groove area, demonstrating strong predictive accuracy with a coefficient of determination (R²) of 0.91288 when validated against empirical data. The proposed model provides a robust framework for designing motorcycle tires with enhanced performance and safety on wet road conditions.